The Interorganizational Network as a Political Economy - Benson, J. Kenneth (Administrative Science Quarterly, 1975)
J. Kenneth Benson The interorganizational network may be conceived as a political economy concerned with the distribution of two scarce resources, money and authority. Organizations, as participants in the political economy, pursue an adequate supply of resources. Interactions and sentiments of organizations are dependent upon their respective market positions and power to affect the flow of resources. The interorganizational network is itself linked to a larger environment consisting of authorities, legislative bodies, bureaus, and publics. The flow of resources into the network depends upon developments in this larger environment.